2017
DOI: 10.1039/c7ra02148h
|View full text |Cite
|
Sign up to set email alerts
|

Influence of normal load on the three-body abrasion behaviour of monocrystalline silicon with ellipsoidal particle

Abstract: Currently, monocrystalline silicon has been widely applied in micro-electro-mechanical systems (MEMSs).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 43 publications
0
9
1
Order By: Relevance
“…It is noteworthy that the critical axial ratio maybe varies under different conditions with respect to key parameters, such as temperature, normal load, and sliding velocity [40,41]. Furthermore, with the decrease of axial ratio, the friction coefficient increases obviously and even larger than 1.0 for the sliding particle, which is much larger than experimental results.…”
Section: Movement Pattern Of Abrasive Particlecontrasting
confidence: 46%
See 1 more Smart Citation
“…It is noteworthy that the critical axial ratio maybe varies under different conditions with respect to key parameters, such as temperature, normal load, and sliding velocity [40,41]. Furthermore, with the decrease of axial ratio, the friction coefficient increases obviously and even larger than 1.0 for the sliding particle, which is much larger than experimental results.…”
Section: Movement Pattern Of Abrasive Particlecontrasting
confidence: 46%
“…When the axial ratio reduced from a large value and then passed over the critical value, the abrasive particle would slide changing from rolling. It is noteworthy that the critical axial ratio maybe varies under different conditions with respect to key parameters, such as temperature, normal load, and sliding velocity [40,41].…”
Section: Movement Pattern Of Abrasive Particlementioning
confidence: 99%
“…When the axial ratio reduced from a large value and then passed over the critical value, the abrasive particle would slide changing from rolling. It is noteworthy that the critical axial ratio maybe varies under different conditions with respect to key parameters such as temperature, normal load and sliding velocity [37,38]. Furthermore, with the decrease of axial ratio, the friction coefficient increases obviously and even larger than 1.0 for the sliding particle, which is much larger than experimental results.…”
Section: Movement Pattern Of Abrasive Particlementioning
confidence: 77%
“…In fact, Shi et al [34] pointed out that sliding motion could generate superior quality surface and increase efficiency during the CMP operation. Si et al [35] reported that both sliding and rolling movements play major parts in the material removal mechanism.…”
Section: Introductionmentioning
confidence: 99%